Environmental risk factors and cardiovascular diseases: a comprehensive expert review. Issue 14 (5th October 2021) - Münzel, Thomas; Hahad, Omar; Sørensen, Mette; Lelieveld, Jos; Duerr, Georg Daniel; Nieuwenhuijsen, Mark; Daiber, Andreas
Abstract: Non-communicable diseases (NCDs) are fatal for more than 38 million people each year and are thus the main contributors to the global burden of disease accounting for 70% of mortality. The majority of these deaths are caused by cardiovascular disease (CVD). The risk of NCDs is strongly associated with exposure to environmental stressors such as pollutants in the air, noise exposure, artificial light at night, and climate change, including heat extremes, desert storms, and wildfires. In addition to the traditional risk factors for CVD such as diabetes, arterial hypertension, smoking, hypercholesterolaemia, and genetic predisposition, there is a growing body of evidence showing that physicochemical factors in the environment contribute significantly to the high NCD numbers. Furthermore, urbanization is associated with accumulation and intensification of these stressors. This comprehensive expert review will summarize the epidemiology and pathophysiology of environmental stressors with a focus on cardiovascular NCDs. We will also discuss solutions and mitigation measures to lower the impact of environmental risk factors with focus on CVD. Graphical Abstract: